Penerapan Media Video Tutorial Pada Kompetensi Dasar Sulaman Aplikasi Di Kelas XI SMK Dharma Wanita Gresik - Risna Taftiyana Dewi; Yulistiana Yulistiana; Deny Arifiana; Ma’rifatun Nashikhah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The media is one important factors in learning activities. Learning media is an intermediary between educators and students in delivering materia. The aim of this research were (1) to describe the implementation of leraning by applying video tutorial media to the basic competence of application embroidery (2) to describe student learning outcomes in the basic competence of application embroidery after applying video tutorials (3) to describe student responses to video tutorials on the basic competence of application embroidery. The type of research is pre-experimental with design one shot case study.this research was conducted at Dharma Wanita Vocational School Gresik in class XI fashion design in the odd semester of the 2022/2023 school years. The data collection method used is the observation method, the questionnaire method, and the test method for learning outcomes. Based on the result data analysis, the implementation of learning by applying video tutorial media was obtained from the assessment of 2 observers 0f 97, 7% for teacher activities and 89,5% for student activities which were declared very good. Student learnimg outcomes were stated to have completed the KKM with average 0f 84, 62. Student responses to the video tutorial media that wer eapplied obtained an average percentage of 93, 75% including very good category.